Makna dan Mitos Pernikahan dalam Lirik Lagu "Lagu Pernikahan Kita" oleh Tiara Andini dan Arsy Widianto: Kajian Semiotik Roland Barthes - Citrayomie, Ayoedia Gita; Budipratiwi , Rizki Ayu; Rosdiana , Rosdiana; Tarigan , Veronika Ita Karina (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2025)
In this study, Roland Barthes’ semiotic technique is used to analyze the symbolism of marriage in the lyrics of Lagu Pernikahan Kita performed by Tiara Andini and Arsy Widianto. The song functions as a communication tool, using its lyrics to convey emotions and ideas. The significance of this work is reflected in its popularity. With an interpretative perspective and qualitative methodology, the study focuses on the use of language to understand meaning. Without conducting interviews, data is collected through document analysis, specifically by examining the song lyrics. The findings show that, at the denotative level, the lyrics depict sacred moments of marriage, happiness, the couple’s aspirations, and their dedication to a lifelong relationship. The lyrics convey deep metaphorical meanings of marriage as a life journey, expressing a profound longing for lifelong love, togetherness, and emotional support. Finally, at the mythic level, the lyrics reinforce the cultural perspective that marriage is the pinnacle of romantic relationships and a symbol of emotional maturity. Lagu Pernikahan Kita functions not only as entertainment but also as a cultural text that reflects and constructs social values and the ideology of marriage within the Indonesian context. A deep understanding of its meaning is essential to reveal the cultural and communicative functions contained within it.